Perdagangan Daun Kratom di Marketplace Shopee Perspektif Fatwa DSN-MUI NO.146/DSN-MUI/XII/2021 Tentang Online Shop Berdasarkan Prinsip Syari’ah - Tasya Putri Nabilla Ritonga; Muhammad Ramadhan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The unclear legal position of kratom (Mitragyna Speciosa Kort) in Indonesia creates a grey area in law enforcement and regulation. Although BPOM has banned the use of kratom in traditional medicine and health supplements through Letter Number HK.044.42.09.16.1740 of 2016, and BNN has recommended kratom as a class I narcotic since 2019, regulatory contradictions arise when Permendag Number 20 and 21 of 2024 actually regulate the export trade of kratom. This phenomenon allows kratom trade to take place freely on e-commerce platforms such as Shopee, which has the potential to violate sharia principles in online trading. The study aims to analyze the practice of kratom trading and the monitoring system of the Shopee platform, as well as to analyze kratom trading in the Shopee marketplace from the perspective of DSN-MUI fatwa No. 146 / DSN-MUI / XII / 2021. The study uses a normative juridical method with a statute approach and a conceptual approach. Data is obtained through literature studies and then processed using deductive thinking logic. The results of the study show that in March 2025, at least 20 online stores were identified that were actively trading kratom on Shopee in various forms, from powder to capsules ranging from IDR 35,000 to IDR 100,000. The sellers used vague terms such as ("daun purik", "daun purli"), disguised product categories, and minimized information to avoid platform detection. Analysis based on DSN-MUI Fatwa No. 146 / DSN-MUI / XII / 2021 shows that the trade in kratom leaves is not fully in accordance with sharia principles because: the object of the transaction contains psychoactive compounds whose halal status is in doubt; legal status is in a gray zone without a BPOM distribution permit; sales practices that hide risks and side effects (tadlis and ghisysy); and the potential for dharar which is contrary to the principles of Islamic jurisprudence to prevent harm. This study concludes that there is a need for stricter supervision and stricter harmonization of regulations to ensure compliance with sharia provisions.